Water molecule attachment mode on the dried polysaccharide influences its free radical scavenging ability. (April 2020) - Yang, Jingfeng; Wang, Yanan; Yin, Ruocheng; Pang, Jiayao; Cong, Yaqi; Yang, Sheng
Graphical abstract: Highlights: Three methods dried polysaccharide showed different antioxidant activities. All tests including, DPPH, OH and ABTS showed the same tendency. They showed similar characteristic in FT-IR and X-ray diffraction spectrum. They have different interaction patterns with water in LF-NMR spectrum. Abstract: In this study, we extracted polysaccharide from Sporophyll of Undaria pinnatifida Suringar and performed it to reveal the effect of dehydration mode on polysaccharide free radical scavenging ability. The polysaccharide extract was dried by vacuum freeze-drying, vacuum drying and hot-air drying methods, respectively. The result elucidated that these products by three kinds of drying methods showed different clearance abilities in DPPH, OH and ABTS scavenging free radicals tests, with the following order: vacuum freeze-drying > vacuum drying > hot-air drying. They showed similar characteristic in Infrared Spectroscopy and X-ray Diffraction spectrum, but have different interaction patterns with water in Low Field Nuclear Magnetic Resonance. The scavenging ability difference may due to the amount of bound water and immobilized water in dried status. The absence of immobilized water on polysaccharide would facilitate the functional groups to reach to the free water molecule and help for the polysaccharide to form triple helix stereo-configuration in solution.